Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry imaging of ochratoxin A and fumonisins in mold-infected food - Hickert, Sebastian; Cramer, Benedikt; Letzel, Matthias C.; Humpf, Hans-Ulrich (Rapid communications in mass spectrometry, 2016)
Rationale Mycotoxins are toxic secondary metabolites produced by various fungi. Their distribution within contaminated material is of high interest to obtain insight into infection mechanisms and the possibility of reducing contamination during food processing. Methods Various vegetable foodstuffs were infected with fungi of the genera Fusarium and Aspergillus. The localization of the produced mycotoxins was studied by matrix‐assisted laser desorption/ionization time‐of flight mass spectrometry imaging (MALDI‐MSI) of cryosections obtained from infected material. The results were confirmed by high‐performance liquid chromatography/electrospray ionization triple quadrupole mass spectrometry (HPLC/MS/MS). Results The mycotoxins ochratoxin A (OTA) and fumonisins of the B‐ and C‐series (FB1, FB2, FB3, FB4, FC1, FC2/3, and FC4) as well as partially hydrolyzed fumonisins (pHFB1, pHFB2, pHFB3, pHFC1, and pHFC2/3) could successfully be detected by MALDI‐MSI in mold‐infested foodstuffs. The toxins are distributed differently in the material: OTA is co‐localized with visible fungal spoilage while fumonisins could be detected throughout the whole sample. Conclusions This work shows the applicability of MALDI‐MSI to mycotoxin analysis. It has been demonstrated that the analyzed mycotoxins are differently distributed within moldy foodstuffs. These findings show the potential of MALDI‐MSI for the localization of these hazardous compounds in various plant tissues. Copyright © 2016 John Wiley & Sons, Ltd.